Quantitative differentiation of thoracolumbar transitional vertebrae : possible embryological origins and associations with other anomalies in the vertebral column - Keough, Natalie (University of Pretoria, 2022)
Thesis (PhD (Anatomy))--University of Pretoria, 2021.